2003
DOI: 10.1023/a:1023274532456
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Following lung injury, red blood cells (RBC) may interact with extracellular matrix (ECM). Fibroblasts, the resident cell in the ECM, have the capacity to produce and secrete a variety of mediators including interleukin-8 (IL-8). In the present study we hypothesized that RBC, or soluble factors released from them, may stimulate IL-8 production by fibroblasts. Fibroblasts were cultured in a three-dimensional collagen gel culture system in the presence or absence of RBC or conditioned medium from RBC (RBC-CM). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Very few studies have determined the content or activity of RBC conditioned media. One study reported that T cell proliferation was stimulated in the presence of RBC conditioned media and that this stimulation was comparable with intact RBC-mediated proliferation 23 and another observed that culturing fibroblasts in the presence of intact RBCs or RBC conditioned media stimulated the secretion of IL-8 and the expression of the corresponding mRNA 8 . This result was also replicated by culturing fibroblasts in the presence of TNF-α and IL-1β, both of which were cytokines detected in the RBC conditioned media in this current study (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Very few studies have determined the content or activity of RBC conditioned media. One study reported that T cell proliferation was stimulated in the presence of RBC conditioned media and that this stimulation was comparable with intact RBC-mediated proliferation 23 and another observed that culturing fibroblasts in the presence of intact RBCs or RBC conditioned media stimulated the secretion of IL-8 and the expression of the corresponding mRNA 8 . This result was also replicated by culturing fibroblasts in the presence of TNF-α and IL-1β, both of which were cytokines detected in the RBC conditioned media in this current study (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The concentrations of released cytokines are summarised in the Supplementary results (Supplementary Table S3 – S4 ). Analysis of RBC conditioned media has not been widely reported in the scientific literature, but its effect on T cells and fibroblasts has been briefly reported 8 , 23 . However, the cytokine profile of the conditioned media in these studies was not investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myodifferentiation and fibrosis are particularly important in airway remodeling and asthma as they can lead to exacerbated symptoms and progressive damage (Grinnell, 2000; Hinz et al, 2007). To better understand how fibroblasts are affected by soluble factors from other types of cells in airway remodeling, researchers have conducted mixed coculture (embedding additional cell types into the fibroblasts-laden collagen), conditioned media coculture (feeding fibroblast-laden gel matrix with supernatants collected from other types of cells), and segregated Transwell coculture CGC experiments (Fredriksson et al, 2003; Zagai et al, 2007; Margulis et al, 2009; Wygrecka et al, 2013). These studies revealed that mast cells, red blood cells, and eosinophils can promote fibroblast contraction in mixed 3D coculture, or in conditioned media culture through paracrine signaling; whereas blood monocytes and lung epithelial cells attenuate fibroblast-mediated gel contractility, an important aspect of tissue repair (Sköld et al, 2000; Epa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, fibroblasts respond vigorously to the early inflammatory response mediators IL-1β and TNF-α 28,29. These mediators induce a number of responses in fibroblasts including release of the cytokines IL-6,10 IL-8,30 and MMPs 16. Thus, fibroblasts may participate in the amplification of IL-1β and TNF-α-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%